Manipulating the hydrogen evolution pathway on composition-tunable CuNi nanoalloys. Issue 2 (12th December 2016) - Lin, Zhaoyong; Li, Jiling; Li, Lihua; Yu, Lili; Li, Weijia; Yang, Guowei
Abstract : CuNi nanoalloys with cocatalytic activities comparable to Pt for TiO2 photocatalytic H2 evolution were investigated based on the hydrogen evolution pathway. Abstract : The supply of clean hydrogen energy through photocatalysis in the future requires the finding of low-cost, efficient and durable cocatalysts to replace noble metal Pt. Cu and Ni are believed to be two promising materials. However, their cocatalytic performance is still limited. The theory of the hydrogen evolution pathway on Cu and Ni surfaces reveals that Cu can release H2 molecules easily but capture H atoms and photoelectrons with difficulty, while Ni performs inversely. To overcome this issue, we consider that improved cocatalytic performance could be achieved by the substitution of Ni atoms into a Cu crystal lattice to form a CuNi alloy. Here, we reported that CuNi alloy nanoparticles were prepared by a process of laser ablation in liquid (LAL). Their compositions could be tuned by varying the concentration of the isopropanol aqueous solution, which is novel in LAL. We demonstrated that the photocatalytic H2 evolution performance of TiO2 nanorods can be greatly improved by loading these CuNi nanoalloys on them to act as cocatalysts. Furthermore, these cocatalysts present favorable stability. The best cocatalytic performance was achieved by Cu63 Ni37 alloy nanoparticles, even better than Pt. First-principles calculations demonstrated that the Cu63 Ni37 alloy nanoparticles possess a high H atom adsorption energy, a large work function and a small H2 molecule adsorption energy, resulting in the rational manipulation of the hydrogen evolution pathway and the optimal cocatalytic performance. This work provided a strategy to design cheap, robust and durable cocatalysts for photocatalytic H2 evolution.